International Efforts to Document Genocide Crimes - Mahdi, Najm (Journal of Legal Sciences, 2026)
Genocide is the first and most serious of the four major crimes stipulated in Article 5 of the Statute of the International Criminal Court. It is a heinous crime against humanity that aims to destroy, in whole or in part, a group of people because of their membership in a particular ethnic, religious, national, or racial group. It is one of the most horrific crimes that a person can commit against another person. The study aims to define the crime of genocide, its pillars, explain the most important agreements that address the crime of genocide, clarify the pillars of this crime, and impose penalties for this crime. Since the aim of the study is to shed light on the crime of genocide, this research relied on the analytical approach by presenting and analyzing the rules of international humanitarian law and international criminal law, and the descriptive approach to clarify international legal theories and rules related to this horrific crime. The research will conclude with the findings and recommendations of this study.